Intervocalic /r/ and pre-consonantal /r/ in Penang Malay dialect: an instrumental analysis - Abdul Latiff, Muhamad Farid (Kolej Universiti Islam Selangor (KUIS), 2017)
This paper makes an instrumental analysis of intervocalic /r/ and pre-consonantal /r/ in Penang Malay Dialect produced by two Malaysian Malay undergraduate speakers. The focus is on the vowel quality of intervocalic /r/ and pre-consonantal /r/ which includes three levels of analysis: perception analysis, acoustic analysis, and phonological rules. The formant frequency model (following Watt and Tillotson 2001) was used to analyze the vowels on PRAAT version 6.0.29 (Boersma, Paul, Weenink, & David, 2017). The results indicate that, the speakers had produced the intervocalic /r/ as /ʁ/ in Penang Malay Dialect. However, for pre-consonantal /r/, the production of the sound was dynamic because the speakers had produced it differently. The acoustic analysis shows a significant difference in the formant values (F1 and F2) between intervocalic /r/ and pre-consonantal /r/.